Dennis Engels: A Humanitarian and Ethical Scholar. Issue 1 (April 2015) - Ohrt, Jonathan H.
<x xml:space="preserve">Abstract</x> Dr. Dennis Engels retired in 2011 after a 35‐year career as a counselor educator, during which he contributed over 30 years of service to the Association for Spiritual, Ethical, and Religious Values in Counseling. In this profile article, the author reviews the highlights of Dr. Engels's distinguished career and presents an interview in which Dr. Engels discusses (a) his journey as a counselor educator, (b) ethical standards and credentialing, and (c) the future of counseling.